Performance of Concrete Containing Glass and Nylon Fibers - Hashim, Norhashimah; Sheikh Khalid, Faisal (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete is the most important material that include composite material with a combination of cement, course and fine aggregate and water. In fact of revolution of concrete, a lot has happen from ancient times to the present. Various types of additives have been placed in the concrete according to the needs of the structure and have their respective advantages. Fibers are primarily used as replacements for conventional reinforcement in non-structural applications to control early thermal contraction and drying shrinkage cracking. The use of fibers as a part of structural applications is continuously increasing. The addition of combination between glass and nylon fibers in concrete can enhance its strength and make it more durable. Therefore, this study was investigated the strength properties of concrete containing glass and nylon fibers as addition fiber materials. The design addition of fiber which is 0%, 0.5%, 1.0% and 1.5% for both type of fiber was evaluated in 7 and 28 days. Water cement ratio of 0.5 was used in this study. Concrete containing 1% glass fiber and 1% nylon fiber was the optimum compressive and tensile strength tests. Therefore, the combination of glass and nylon fiber in mix proportion of concrete was increase the performance of concrete than the normal concrete.